Type I Fracture Toughness Test of Rock-like Materials Based on the Particle Flow Method - Ling Yue; Bangyong Yu; Chengxi Zhao; Fei Guo; Fei Huang (Advances in Civil Engineering)
In order to investigate the feasibility and reliability of the three-dimensional particle flow method in simulating the type I fracture toughness test, four types of numerical samples were established by particle flow code PFC3D: straight crack three-point bending (SC3PB), edge cracked flattened semicircular disc (ECFSD), cracked chevron notched Brazilian disc (CCNBD), and edge cracked flattened ring (ECFR). Three models with different strength parameters (group A, group B, and group C) were established for each type, in which group A parameters are obtained from the concrete model, group B parameters are applied for simulating marble, and group C parameters are for granite. The type I fracture toughness and the failure form of each model are obtained by conducting the numerical test, and the curves of load versus displacement of loading point are recorded. The numerical test results show that, with the same strength parameter, the maximum difference in test results of each specimen type is 0.39 MPa·m1/2. The KIC of ECFR specimen is 0.13–0.28 MPa·m1/2 smaller than that of CCNBD specimen, and the KIC of ECFSD specimen is slightly higher than that of CCNBD sample. The KIC of SC3PB specimen is 0.06–0.21 MPa·m1/2 smaller than that of the CCNBD sample. When the loading rate is less than 0.01 m/s, the effect of loading rate on fracture toughness can be reduced to less than 0.1 MPa·m1/2.